Endotheliopathy in COVID-19-associated coagulopathy: evidence from a single-centre, cross-sectional study - Goshua, George (Lancet Haematol, 2020)
BACKGROUND: An important feature of severe acute respiratory syndrome coronavirus 2 pathogenesis is COVID-19-associated coagulopathy, characterised by increased thrombotic and microvascular complications. Previous studies have suggested a role for endothelial cell injury in COVID-19-associated coagulopathy. To determine whether endotheliopathy is involved in COVID-19-associated coagulopathy pathogenesis, we assessed markers of endothelial cell and platelet activation in critically and non-critically ill patients admitted to the hospital with COVID-19. METHODS: In this single-centre cross-sectional study, hospitalised adult (≥18 years) patients with laboratory-confirmed COVID-19 were identified in the medical intensive care unit (ICU) or a specialised non-ICU COVID-19 floor in our hospital. Asymptomatic, non-hospitalised controls were recruited as a comparator group for biomarkers that did not have a reference range. We assessed markers of endothelial cell and platelet activation, including von Willebrand Factor (VWF) antigen, soluble thrombomodulin, soluble P-selectin, and soluble CD40 ligand, as well as coagulation factors, endogenous anticoagulants, and fibrinolytic enzymes. We compared the level of each marker in ICU patients, non-ICU patients, and controls, where applicable. We assessed correlations between these laboratory results with clinical outcomes, including hospital discharge and mortality. Kaplan–Meier analysis was used to further explore the association between biochemical markers and survival. FINDINGS: 68 patients with COVID-19 were included in the study from April 13 to April 24, 2020, including 48 ICU and 20 non-ICU patients, as well as 13 non-hospitalised, asymptomatic controls. Markers of endothelial cell and platelet activation were significantly elevated in ICU patients compared with non-ICU patients, including VWF antigen (mean 565% [SD 199] in ICU patients vs 278% [133] in non-ICU patients; p<0·0001) and soluble P-selectin (15·9 ng/mL [4·8] vs 11·2 ng/mL [3·1]; p=0·0014). VWF antigen concentrations were also elevated above the normal range in 16 (80%) of 20 non-ICU patients. We found mortality to be significantly correlated with VWF antigen (r = 0·38; p=0·0022) and soluble thrombomodulin (r = 0·38; p=0·0078) among all patients. In all patients, soluble thrombomodulin concentrations greater than 3·26 ng/mL were associated with lower rates of hospital discharge (22 [88%] of 25 patients with low concentrations vs 13 [52%] of 25 patients with high concentrations; p=0·0050) and lower likelihood of survival on Kaplan–Meier analysis (hazard ratio 5·9, 95% CI 1·9–18·4; p=0·0087). INTERPRETATION: Our findings show that endotheliopathy is present in COVID-19 and is likely to be associated with critical illness and death. Early identification of endotheliopathy and strategies to mitigate its progression might improve outcomes in COVID-19. FUNDING: This work was supported by a gift donation from Jack Levin to the Benign Hematology programme at Yale, and the National Institutes of Health.